An improved MASH sigma-delta modulator with all-anolog interstage and input-feedforward architecture. (16th November 2020) - Ge, Li-Jun; Qiao, Ze Jun; Wang, Jun; Li, Ming Zhou; Zhu, De-Bao; Dai, Bo; Zhao, Qing Qing
ABSTRACT: This paper puts forward an improved multi-stage noise-shaping (MASH) sigma-delta modulator. Derived from a fourth-order two-stage MASH architecture with adder-less architecture of cascade of integrators with feedforward (CIFF), the proposed modulator improves the method of extracting quantization noise of the first stage to form an all-analog interstage, and two input-feedforward paths are added to the second stage to reduce the output swing of the integrator. Analyses and measurements indicate that the proposed architecture has lower in-band quantization noise power, higher signal-to-quantization noise ratio (SQNR), and lower power consumption and complexity as well. When operating from a 1.2 V supply, the modulator achieves 107.56 dB peak SQNR, 71.8 dB peak Signalnoise and distortion ratio while consuming 26 mW, with an OSR of 8 at a 160 MHz sampling frequency.